2021
DOI: 10.5194/acp-21-1127-2021
|View full text |Cite
|
Sign up to set email alerts
|

Toward closure between predicted and observed particle viscosity over a wide range of temperatures and relative humidity

Abstract: Abstract. Atmospheric aerosols can exist in amorphous semi-solid or glassy phase states whose viscosity varies with atmospheric temperature and relative humidity. The temperature and humidity dependence of viscosity has been hypothesized to be predictable from the combination of a water–organic binary mixing rule of the glass transition temperature, a glass-transition-temperature-scaled viscosity fragility parameterization, and a water uptake parameterization. This work presents a closure study between predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 79 publications
3
44
0
Order By: Relevance
“…Furthermore, for molar masses greater than 200 g mol –1 , D f is typically in the range of 5–20 and approaches a limit of ∼10 at molar masses greater than 400 g mol –1 . The value of D f was assumed to be independent of RH. , This assumption was consistent with previous studies which found that the values of D f in sucrose and citric acid were independent of water content, except when the water content was very low. ,, After T 0 (RH) was calculated, we calculated η­(RH, T ) using eq .…”
Section: Materials and Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, for molar masses greater than 200 g mol –1 , D f is typically in the range of 5–20 and approaches a limit of ∼10 at molar masses greater than 400 g mol –1 . The value of D f was assumed to be independent of RH. , This assumption was consistent with previous studies which found that the values of D f in sucrose and citric acid were independent of water content, except when the water content was very low. ,, After T 0 (RH) was calculated, we calculated η­(RH, T ) using eq .…”
Section: Materials and Methodssupporting
confidence: 66%
“…52,70−72 This assumption was consistent with previous studies which found that the values of D f in sucrose and citric acid were independent of water content, except when the water content was very low. 68,73,74 After T 0 (RH) was calculated, we calculated η(RH, T) using eq 4.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a 1 lm particle and a 0.5 L min À1 flow rate the calculated transmission is 0.0765, based on a critical mobility of 1.8 Â 10 9 m 2 V À1 s À1 and z DMA of 1.1 Â 10 9 m 2 V À1 s À1 . The primary use for the EP described here is to remove charged particles in the dual tandem DMA [16,19,22,39]. Traditionally, EPs have been used for estimating the neutral fraction after passage through a bipolar neutralizer.…”
Section: Resultsmentioning
confidence: 99%
“…The primary use for the EP described here is to remove charged particles in the dual tandem DMA [16] , [19] , [22] , [39] . Traditionally, EPs have been used for estimating the neutral fraction after passage through a bipolar neutralizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation